2015
DOI: 10.1016/j.sjopt.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the treatment of central serous chorioretinopathy

Abstract: Central serous chorioretinopathy is a disease that is partly understood. Novel advancements have led to further understanding of the disease, and have identified choroidal dysfunction as the principal element in CSCR development. New imaging tools have aided in better monitoring disease response to various treatment models. Enhanced depth imaging optical coherence tomography, in particular, has helped in observing choroidal thickness changes after various treatment models. To date, photodynamic therapy and foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 120 publications
0
31
0
1
Order By: Relevance
“…However, those who do not resolve spontaneously may develop permanent visual impairment because of pigment epithelial and photoreceptor damage [6]. Most clinicians prefer to observe these patients for three months before considering any treatment options because most cases recover spontaneously [7][8][9]. Infrequently, neurosensory retinal detachment persists and leads to RPE and photoreceptor damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, those who do not resolve spontaneously may develop permanent visual impairment because of pigment epithelial and photoreceptor damage [6]. Most clinicians prefer to observe these patients for three months before considering any treatment options because most cases recover spontaneously [7][8][9]. Infrequently, neurosensory retinal detachment persists and leads to RPE and photoreceptor damage.…”
Section: Introductionmentioning
confidence: 99%
“…It has a benign and self-limiting nature, with a long-term recurrence rate of 30%. CSCR usually occur in males in 20-50 years [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the pathogenesis of disease is well unknown, it has been considered that focal RPE defect or choroidal lobular ischemia and choroidal venous congestion may be played in the main role [5][6][7][8]. Recent studies have demonstrated that the CSC is associated with psychological stress, type A personality, glucocorticoid treatment, endogenous hypercortisolism like Cushing's syndrome, systemic hypertension, and pregnancy [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However 50% of the patients have recurrences and 15-20% progress to chronic form which has relatively poor visual outcome 12. Various treatment modalities such as standard laser photocoagulation, micro-pulse diode laser photocoagulation, trans-pupillary thermotherapy (TTT), photodynamic therapy (PDT)and multiple anti-corticosteroids agents have been proposed for the treatment of CSCR 13. A recent study documented mineralocorticoid receptors in choroidal tissue, and hypothesized that glucocorticoids activate mineralocorticoid receptors and may cause or aggravate CSCR manifestations [Zhao M et al 2012] 14.…”
Section: Introductionmentioning
confidence: 99%